2008
DOI: 10.1111/j.1365-2958.2008.06216.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tafazzin in yeast leads to increased oxidative stress during respiratory growth

Abstract: SummaryThe tafazzin (TAZ) gene is highly conserved from yeast to humans, and the yeast taz1 null mutant shows alterations in cardiolipin (CL) metabolism, mitochondrial dysfunction and stabilization of supercomplexes similar to those found in Barth syndrome, a human disorder resulting from loss of tafazzin. We have previously shown that the yeast tafazzin mutant taz1D, which cannot remodel CL, is ethanol-sensitive at elevated temperature. In the current report, we show that in response to ethanol, CL mutants ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 63 publications
6
73
0
Order By: Relevance
“…Indeed, the largest Taz1p complex was readily detected in the lactatederived wt extracts compared with the dextrose-derived wt mitochondrial extracts. Notably, mitochondria grown in dextrose versus lactate contained significantly less CL (Figure 7C), as reported previously (Gu et al, 2004;Chen et al, 2008). Therefore, whether the large Taz1p complex requires a certain threshold of CL for its stability or the abundance of the large Taz1p complex is below the level of detection in dextrose-derived mitochondrial extracts is unclear.…”
Section: Probing the Functional Relevance Of The Defined Taz1p Interamentioning
confidence: 54%
“…Indeed, the largest Taz1p complex was readily detected in the lactatederived wt extracts compared with the dextrose-derived wt mitochondrial extracts. Notably, mitochondria grown in dextrose versus lactate contained significantly less CL (Figure 7C), as reported previously (Gu et al, 2004;Chen et al, 2008). Therefore, whether the large Taz1p complex requires a certain threshold of CL for its stability or the abundance of the large Taz1p complex is below the level of detection in dextrose-derived mitochondrial extracts is unclear.…”
Section: Probing the Functional Relevance Of The Defined Taz1p Interamentioning
confidence: 54%
“…In a previous study, we showed that the loss of CL leads to decreased stability of respiratory supercomplexes (9), which is expected to cause increased ROS formation. Consistent with this, protein carbonylation, a sensitive marker of intracellular ROS, was significantly increased in crd1⌬ (84). Therefore, we addressed the possibility that the iron-associated growth defects in crd1⌬ cells may result from increased ROS.…”
Section: Increased Expression Of Atm1 Does Not Rescue Iron Defects Inmentioning
confidence: 61%
“…7). Furthermore, we observed elevated expression of the iron regulon genes even in fermentative growth conditions, during which protein carbonylation in CL mutants is not increased (84). In addition, expression of antioxidant genes is not increased during these growth conditions in crd1⌬ (supplemental Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…In an experimental model of heart failure, the decrease of oxidative phosphorylation has been associated with a decrease of respiratory supercomplexes (62,63,64). Lymphoblasts from patients affected by Barth Syndrome, due to genetic loss of tafazzin, an enzyme involved in cardiolipin remodeling, have altered mitochondrial supercomplexes (50); likewise, in a yeast experimental model of tafazzin mutation, Chen et al (14) observed an increased oxidative stress in response to ethanol. Aging is also accompanied by a decline of supercomplex association (25,32); despite some uncertainties and challenges, aging is generally associated with increased ROS and oxidative damage (for a recent review cf.…”
mentioning
confidence: 99%